2012
DOI: 10.1038/nrcardio.2012.91
|View full text |Cite
|
Sign up to set email alerts
|

Heartache and heartbreak—the link between depression and cardiovascular disease

Abstract: The close, bidirectional relationship between depression and cardiovascular disease is well established. Major depression is associated with an increased risk of coronary artery disease and acute cardiovascular sequelae, such as myocardial infarction, congestive heart failure, and isolated systolic hypertension. Morbidity and mortality in patients with cardiovascular disease and depression are significantly higher than in patients with cardiovascular disease who are not depressed. Various pathophysiological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
305
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(319 citation statements)
references
References 160 publications
9
305
0
5
Order By: Relevance
“…SES and psychosocial factors, including depressive symptoms, psychological distress, and perceived stress, have been increasingly recognized as risk factors for CVD 3, 4, 7. Only recently have researchers begun to appreciate the information to be learned by considering both sets of factors simultaneously to better identify persons at elevated risk of poor cardiovascular outcomes and mortality 21, 23, 24, 25, 41.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SES and psychosocial factors, including depressive symptoms, psychological distress, and perceived stress, have been increasingly recognized as risk factors for CVD 3, 4, 7. Only recently have researchers begun to appreciate the information to be learned by considering both sets of factors simultaneously to better identify persons at elevated risk of poor cardiovascular outcomes and mortality 21, 23, 24, 25, 41.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence, however, has demonstrated that psychosocial factors also contribute to the development of CVD 3. In particular, depression4, 5, 6 and perceived psychosocial stress7, 8, 9 have been linked to increased CVD risk, and some research has demonstrated that the confluence of these 2 factors may be particularly deleterious for cardiovascular health 10, 11, 12. This latter finding is consistent with a recently proposed psychosocial “perfect storm13” model 13 of CVD risk that suggests an underlying vulnerability (eg, depression) is associated with greater risk of cardiac events and mortality, particularly in the presence of perceived stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of psychiatric comorbidity on illness, treatment outcomes, and use of healthcare resources has been studied in great detail in certain fields of medicine, predominantly cardiology and neurology [10,17,28,34]. Depression has been linked to an increased mortality rate after myocardial infarction, cerebrovascular disease, and cancer [32].…”
Section: Introductionmentioning
confidence: 99%
“…Ageing (which increases the odds of both conditions), lifestyle factors, inflammation pathways, heart rate variability, impaired arterial repair and several genes, are just some of the mechanisms that could play a role. 14 Nevertheless, the link is well established. A review by the American Heart Association 15 recently recommended that depression be considered an independent risk factor for adverse outcomes in patients with acute coronary syndrome, given the strength of the evidence in the current literature.…”
Section: Depressionmentioning
confidence: 99%